A Trajectory of Ḥalāl Industry in Nigeria: Opportunities and Challenges - Adamu Abubakar Muhammad; Abiola Muideen Lateef; Aliyu Ibrahim; Reza Fahmi; Abubakar Aliyu Yakub; Mahmood Ahmed (CV Media Inti Teknologi, 2025)
Background of study: Ḥalāl industry is an emerging sector with great potential for growth and economic development in Nigeria. The large Muslim population is a driving factor that creates opportunities for its growth to improve the national economy. However, these opportunities, as well as the impeding challenges, have still been poorly understood.Aims and scope of paper: This paper seeks to examine the opportunities and challenges posed by the Ḥalāl industry in Nigeria. It provides a comprehensive review of the sector, outlining its structure, current state, potential for growth and the intimidating challenges.Methods: The paper draws data from both primary and secondary sources; obtained from interviews, industry literature, and government reports.Result: The results show that although Nigeria has a lot of promise because of its Muslim consumer base, agricultural products, and enterprising populace, the sector is still fragmented. Lack of public knowledge, poor infrastructure, low adherence to international ḥalāl norms, and the absence of a national ḥalāl authority are some of the main obstacles. However, prospects in export markets, agro-processing, Islamic financing assistance, youth-led entrepreneurship, and regional trade agreements like the AfCFTA.Conclusion: The research concludes that, driven by the large Muslim population in Nigeria, the ḥalāl industry has strong potential to boost economic growth through local production, greater exports, and tourism development.